Predation of Atelocynus microtis and Speothos venaticus (Carnivora: Canidae) by Boa constrictor (Squamata: Boidae) in Southwestern Brazil and Southeastern Peru - Renata Leite; Patrick Champagne; Evandro Ferreira (Mammalogy Notes, 2023)
Literature on the predation ecology of Amazonian canids is scarce, especially for the two rarely observed canids; Speothos venaticus (Bush Dog) and Atelocynus microtis (Short-eared Dog). Between 2000 and 2005 we documented one observation of predation of a A. microtis from southeastern Peru and an observation of S. venaticus predation from southwestern Brazil.